A multicentre assessment of prostate MRI quality and compliance with UK and international standards. Issue 11 (November 2019) - Burn, P.R.; Freeman, S.J.; Andreou, A.; Burns-Cox, N.; Persad, R.; Barrett, T.
Abstract : AIM: To assess prostate magnetic resonance imaging (MRI) image quality and compliance with technical standards between centres in the South West region of the UK. MATERIALS AND METHODS: Fifteen imaging sites in the region submitted seven consecutive anonymised MRI studies. These were assessed by two experienced radiologists in consensus. Overall, subjective image quality for T2-weighted imaging (T2W), diffusion weighted imaging (DWI), and dynamic contrast enhancement (DCE) was scored on a five-point Likert scale. Five additional quality parameters were also assessed visually, including image noise, motion, artefact, and distortion. The degree of compliance by each site with 21 published technical standards was also assessed. RESULTS: Ninety-four MRI examinations were reviewed from across all sites (mean 6.3 scans per site, range 5–7). Mean compliance with technical standards was 63% (range 38–86%). Forty-seven percent of sites did not perform DCE. One site used a 3 T scanner. The percentage of patients with overall quality scores of ≥3 (diagnostically acceptable) were 68% for T2W, 81% for DWI, and 60% for both T2W and DWI. Ninety-three percent of the 45 patients who underwent DCE had diagnostically acceptable studies. By scanner age, the percentage of patients with diagnostically acceptable T2W scores was 53% for scanners ≥7 years and 80% when <7 years ( p= 0.006). Comparing individual sites, the mean overall quality scores were 2.9 (range 2.2–4.2) for T2W, 3.2 (1.8–4.7) for DWI, and 3.4 (2.5–4.7) for DCE. CONCLUSION: There is wide variation in compliance with recognised technical standards and image quality across sites. If MRI is to replace biopsy in selected low-risk patients, improvements in image quality may be required. Highlights: There was a large variation in image quality and guideline compliance between sites. 40% of patients had non-diagnostic quality scans. Scanner age inversely correlated with T2W image quality. DCE scored highest for image quality, but was only used in 53% of sites. Image quality needs optimization if MRI is used to rule out cancer or avoid biopsy.